A Reduced Switch Count and THD Analysis in Cascaded H Bridge Multi-level inverter Topology (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Designing of a multilevel inverter is required for power conversion with good efficiency, less switching loss, less THD values related to voltage and current . In a multi-level inverter, the desired output value depends on the harmonic values so as to increase the levels in output. This paper presents a 9-level cascaded H bridge inverter and a reduced number of switching devices.The developed H bridge inverter is analyzed in terms of THD values at different loads. The developed H bridge inverter is compared with PD,POD,APOD techniques in terms of THD values. Based on simulation results it has been observed that the developed H bridge inverter system performs well in terms of voltage and current THD values and achieve good efficiency due to less loss.